2017
DOI: 10.5194/acp-17-4419-2017
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei over the Southern Ocean: wind dependence and seasonal cycles

Abstract: Abstract. Multi-decadal observations of aerosol microphysical properties from regionally representative sites can be used to challenge regional or global numerical models that simulate atmospheric aerosol. Presented here is an analysis of multi-decadal observations at Cape Grim (Australia) that characterise production and removal of the background marine aerosol in the Southern Ocean marine boundary layer (MBL) on both short-term weather-related and underlying seasonal scales.A trimodal aerosol distribution co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 50 publications
9
43
0
Order By: Relevance
“…Figure 12 superimposes the 1-h average time series of total CCN concentrations measured at 0.3% supersaturation. There is a rough coincidence with the time variability of the inorganic marine aerosol concentrations, as expected in this marine environment (Ayers and Gras 1991;Gras and Keywood 2017). The campaign average for CCN concentrations is 392 ± 160 cm -3 , significantly higher than the range of concentrations (40-300 cm -3 ) reported by Andreae et al (1995).…”
Section: The Marine Boundary Layer As a Source Of Marine Aerosols Andsupporting
confidence: 79%
“…Figure 12 superimposes the 1-h average time series of total CCN concentrations measured at 0.3% supersaturation. There is a rough coincidence with the time variability of the inorganic marine aerosol concentrations, as expected in this marine environment (Ayers and Gras 1991;Gras and Keywood 2017). The campaign average for CCN concentrations is 392 ± 160 cm -3 , significantly higher than the range of concentrations (40-300 cm -3 ) reported by Andreae et al (1995).…”
Section: The Marine Boundary Layer As a Source Of Marine Aerosols Andsupporting
confidence: 79%
“…However, the accumulation mode (broadly composed of intermediate particle sizes of 50-500 nm) is composed of a complex mixture of both secondary and primary particles. The relative roles of secondary aerosols produced from biogenic sulfur versus primary sea spray aerosols in regulating cloud properties and amounts above the Southern Ocean is still a matter of debate (Meskhidze and Nenes, 2006;Korhonen et al, 2008;Quinn and Bates, 2011;McCoy et al, 2015;Gras and Keywood, 2017;Fossum et al, 2018). First observations of organic carbon (OC) in size-segregated aerosol samples collected at a coastal site in the Weddell Sea (Virkkula et al, 2006) showed that MSA represented only a few percent of the total OC in the sub-micrometre fraction; recent studies demonstrate that sea bird colonies are also important sources of organic compounds locally (Schmale et al, 2013;Liu et al, 2018) as well as seasonal ice microbiota (Dall'Osto et al, 2017b).…”
Section: Origin and Sources Of Antarctic Aerosolmentioning
confidence: 99%
“…This aerosol category type occurs very frequently during winter months (JJ at 33 %-52 %) but not during the other months (0 %-14 %). Gras and Keywood (2017) showed, using data from Cape Grim, that windgenerated coarse-mode sea salt is an important CCN component year round and from autumn through to mid-spring is the second-most important component, contributing around 36 % to observed CCN; these measurements were taken in the Southern Ocean marine boundary layer.…”
Section: Primary Antarctic Aerosolmentioning
confidence: 99%
“…Thus dry deposition, but to an only minor extent wet deposition (partly associated with clear sky precipitation), would be decisive. Consequently future research activities should also envisage assessing dry deposition velocities at this site, e.g., by gradient and/or eddy correlation studies (Grönlund et al, 2002;Contini et al, 2010). On the other hand, retrieving meaningful historic aerosol concentrations from ice core archives also needs a thorough consideration of snow accumulation since snow accumulation co-determines trace compound concentrations in firn and ice (Fischer et al, 1998), which is evidently governed by the infrequent impact of low-pressure systems (Birnbaum et al, 2006;Schlosser et al, 2010;Welker et al, 2014;Kurita et al, 2016).…”
Section: Discussionmentioning
confidence: 99%